Challenges in Measuring Attention Deficit Hyperactivity Disorder Prevalence in School Children: Methodological Issues and Real-World Barriers - Sabharwal, Mrinalini; Singh, Garima; Dhyani, Mohan (Journal of Neonatal Surgery, 2025)
Background: Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder which is characterised by inattention, hyperactivity and impulsivity. It effects the day to day functioning of an individual, especially children. Although it a wide known disorder, still its prevalence remains unrecognized in India. The aim of the present study is to investigate the difficulties that arise while determining the prevalence of ADHD in schools in Dehradun. Method: We systematically searched PubMed,Scopus, Web of Science, andPsychINFO to find relevant studies to estimate the prevalence of ADHD in India. Results: The main obstacles are a lack of knowledge among parents and educators, a lack of resources and training for educators, the stigma associated with mental health disorders in society, which makes it hard for families to get help, and the assistance that schools provide for diagnosing the disease. The study also draws attention to methodological issues, including the underrepresentation of particular demographics, the use of subjective reporting, and inconsistent diagnostic criteria. Conclusion: Developing effective policy frameworks, guaranteeing early intervention, and enhancing ADHD identification all depend on removing these obstacles, according to the results of our review. This study emphasizes the need for improved mental health education and more cooperation between healthcare practitioners and schools in order to improve ADHD prevalence research in India.